Optical and structural properties of synthesized ZnO nanorods through chemical bath deposition on various substrates - Hanaa Flayeh AL Taay; Yasimine Taha Mohammed; Hind Fadhil Oleiwi (Iraqi Journal of Physics, 2020)
Chemical bath deposition was used to synthesize ZnO nanorods (NRs) on glass and fluorine_doped tin oxide (FTO) substrates. X-ray diffraction was performed to examine the crystallinity of ZnO nanorod. Results showed that ZnO NRs had a wurtzite crystal structure. Field emission scanning electron microscopy images showed that glass sample had rod-like structure distribution with (50 nm) diameter and average length of approximately (700 nm), whereas the FTO-coated glass sample had 25 nm diameter and average length of approximately 950 nm. The direct optical transition band gaps of the glass and FTO_coated glass samples were( 4 and 4.43 eV), respectively. The structural and optical properties of the synthesized ZnO products were described. The grown ZnO NRs have good optical properties. The proposed method is simple, inexpensive, soft, and environmentally friendly compared with other methods, making it appropriate for the large-scale manufacturing of devices and other app1ications.